2017
DOI: 10.4149/neo_2017_309
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP3 inhibits migration and invasion in nasopharyngeal carcinoma by suppressing epithelial mesenchymal transition

Abstract: TNF alpha induced protein 3 (TNFAIP3), a member of zinc finger protein family, is a gene whose expression level is promptly induced by the tumor necrosis factor. In this study, the clinical significance of TNFAIP3 was analyzed based on available samples in The Cancer Genome Atlas database. TNFAIP3 downregulation was associated with distant metastasis and worse patient prognosis. TNFAIP3-overexpressing and TNFAIP3-knockdown NPC cell line models were established through plasmid-mediated overexpression and small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…In addition to detecting gene expression, we found that GINS2 knockdown increased STAT1 and STAT2 protein expression and inhibited tumor migration and proliferation, which was consistent with a previous study. Furthermore, Huang et al reported that overexpression of TNFAIP3 inhibited migration and invasion in nasopharyngeal carcinoma [28]. Our results showed that GINS2 knockdown increased TNFAIP3 protein expression, suggesting that TNFAIP3 may be involved in the effects of GINS2 on NSCLC proliferation and migration.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to detecting gene expression, we found that GINS2 knockdown increased STAT1 and STAT2 protein expression and inhibited tumor migration and proliferation, which was consistent with a previous study. Furthermore, Huang et al reported that overexpression of TNFAIP3 inhibited migration and invasion in nasopharyngeal carcinoma [28]. Our results showed that GINS2 knockdown increased TNFAIP3 protein expression, suggesting that TNFAIP3 may be involved in the effects of GINS2 on NSCLC proliferation and migration.…”
Section: Discussionsupporting
confidence: 62%
“…The correlation between these pathway and tumor progression, including NPC, has been proven in previous studies. Especially, focal adhesion (Liu et al, 2018;Yuan et al, 2019;Yu et al, 2019), apoptosis (Li M. et al, 2019;Liang et al, 2019;Wang et al, 2019;Xie et al, 2019), and the tumor necrosis factor (TNF) signaling pathway (Lu et al, 2011;Ou et al, 2015;Huang et al, 2017;Deng et al, 2018) have been reported to be closely related to NPC development.…”
Section: Discussionmentioning
confidence: 99%
“…Using a mouse xenograft, Lee et al showed that with A20 knockdown lung metastasis of epithelial-like breast cancers could be inhibited, suggesting a role for A20 in TGFβ1-induced epithelial mesenchymal transition (EMT) (68). In nasopharyngeal carcinoma, however, A20 overexpression inhibited migration and invasion by suppressing EMT (48). These observations are of particular interest in chronic lung disease: Although EMT is a 'universal' and normal process during tissue repair, in many chronic respiratory diseases EMT appears deregulated leading to different degrees of fibrosis (reviewed in (107)).…”
Section: Role Of Snps / Mutations On A20 Expression and Functionmentioning
confidence: 99%